THE ROLE AND IMPORTANCE OF THE POLİCE DEPARTMENT İN DİSASTER MANAGEMENT: THE EXAMPLE OF KAHRAMANMARAŞ EARTHQUAKES (Third Sector Social Economic Review, 2024)
After the industrial revolution, cities began to develop in terms of population and economy and quickly became the center of the production and service sector. As a result of this, people today live mostly in cities. The increasing desire of people to live in cities increases the risk that the possible effects and damages of natural disasters will be greater than expected. The February 7, 2023 Kahramanmaraş earthquakes in Turkey are an example of the negative consequences that earthquakes can cause in cities. Turkey has been struggling with natural disasters that cause loss of life and property for years. At this point, the type of natural disaster that is more common and causes more damage in Turkey is earthquakes. This situation indicates that urgent measures should be taken to reduce the possible effects of earthquakes in cities. The disaster management process is gaining importance in order to prevent and reduce the negative effects of earthquakes. In this study, it is examined how the Police Department, which is an important part of the Turkish public administration, is positioned in the disaster management process in combating the negative effects of earthquakes. The Police Department takes an active role in combating earthquakes, especially in post-disaster emergency response and recovery efforts. In addition to debris search and rescue work during earthquakes, it undertakes many tasks related to the post-earthquake process. In this context, the Police Department makes significant contributions to the fight against earthquakes with the work carried out within the cyber, aviation and criminal departments. This study draws attention to the importance of task sharing and coordination between institutions, especially the police department, within the scope of disaster management.
Keywords: Disaster; Earthquake; Police; Disaster Management; Crisis Management